Gas-to-feed revolution: a novel review of the microbial conversion of industrial emissions into sustainable livestock feed - Amalyadi, Rezki; Widiastuti, Lusia Komala (Institute for Research and Community Service (LPPM), Universitas Islam Madura, Indonesia, 2025)
The livestock sector is a major contributor to greenhouse gas emissions, especially through feed production and processing. As demand for animal products increases, the need for sustainable alternatives becomes more urgent. This review explores how the circular bioeconomy (CBE) can reduce environmental impact by using industrial waste gases, such as CO₂, CO, and CH₄, as carbon sources for microbial bioconversion. The review discusses key microbial platforms, including autotrophic bacteria, methanotrophs, and hydrogen-oxidizing bacteria, for their ability to convert gases into biofuels and single-cell protein (SCP). These alternatives offer a more ecofriendly approach to conventional livestock feed. The review also highlights successful industrial applications, safety and regulatory challenges, and emerging biotechnological innovations, such as synthetic biology and co-culture systems. Ultimately, integrating the CBE into livestock systems provides a way to achieve more sustainable, resilient, and efficient food production.